The Contract of Employment: Judicial vs Parliamentary Reform - Sherwood, Craig Paul (Kent Law Review, 2017)
The narrow definition of contract of employment developed by the common law tests has given room for employers to avoid protective legislation for the people that work for them. In the current economic climate that we face today, the impact of globalisation and the UK government’s response to the 2008 economic crash has made this problem far worse that it has been at other points in history. This deep, structural problem requires Parliamentary intervention as the courts have failed to reform the definition of the contract of employment effectively. This article will assess the role of Parliament and the judiciary and discuss which institution should take the primary role in reform of the contract of employment.